Territoires émergents d'Amazonie : analyse comparée des dynamiques territoriales dans le Baixo Amazonas et le Nordeste Paraense - Etienne Polge; René Poccard-Chapuis; Marc Piraux (Confins)
While the deterioration of the Amazon’s resources has drawn much attention, spatial dynamics at stake are still poorly understood. At the crossing of the Amazon of roads and Amazon of rivers classical models, new territorial dynamics are taking shape. To characterize these evolutions, trajectories and current territorial dynamics of two contrasting territories were analyzed with a perception-based regional map-making methodology. Our results show that common dynamics from the two occupation models of Amazonia (rivers and roads) are processing. Through the combination of these new dynamics in their respective contexts, different territories are forming. Three key factors determine it: infrastructure and market development, entrepreneurship dynamics, and regulatory framework implemented by the public authorities. Common and sustainable strategies can be undertaken by local actors to adapt to these factors and manage the territorial dynamics. These strategies can be properly achieved only by knowing the reality of the territories amongst new network of actors, in order to get over past divergences.